(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This study examines the effectiveness of using games and interactive activities to enhance vocabulary retention in language learning environments. The research highlights how game-based learning creates a dynamic, engaging, and student-centered atmosphere that increases motivation, reinforces memory, and encourages active participation. Various types of language games such as matching tasks, word puzzles, role-play activities, and interactive group competitions were analyzed to determine their influence on short-term and long-term vocabulary retention. The findings indicate that game-integrated instruction supports deeper cognitive processing, fosters repeated exposure to target words in meaningful contexts, and strengthens learners’ ability to recall and apply vocabulary independently. The study concludes that incorporating well-structured games and activities into language lessons serves as an effective pedagogical strategy for improving vocabulary acquisition and retention.